Analysis of the Al-Qur’an Memorization Program’s Implementation at the Rumah Tahfidz Al-Haramain Banjarmasin - Nurhaliza, Nida; Darmawan, Herman; Hakti, Faisal; Khairani, Ahmad; Kassim, Zarina (Jurnal Pendidikan Islam, 2024)
Currently, the need for preserving the tradition of memorizing the Qur’an is increasingly urgent amidst the rapid flow of globalization. The tahfidz Al-Qur’an program is one of the important efforts to maintain and preserve the tradition of memorizing the Qur’an in the Muslim community. This study aims to analyze the tahfidz Al-Qur’an program at the Al-Haramain Tahfidz House, Banjarmasin. This study uses a qualitative approach with a field research method, which involves observation, interviews, and documentation. The results of the study indicate that the Al-Haramain Tahfidz House has a vision of becoming a leading institution based on the spirit of the Qur’an with a mission to organize quality tahsin and tahfidz Al-Qur’an programs. The tahfidz program at this institution uses the Talaqqi and Ummi methods, which have proven effective in helping students memorize the Qur’an. The Talaqqi method is used to facilitate memorization, while the Ummi method is applied for tahsin, or reading improvement. This study also revealed that the quality of teaching, the structured learning system, and the support teachers provide to students significantly influence the success of the tahfidz program. Supporting and inhibiting factors in the implementation of the Tahfidz program were also identified. The contribution of this study is to provide in-depth insight into the implementation of an effective tahfidz program and can be a reference for similar institutions in developing Al-Qur’an education programs in the future.